Beyond weight loss after sleeve gastrectomy: improvement in health-related quality of life - Dilektaşlı, Evren (The European Research Journal, 2019)
Objectives: Obesity and related diseases are increasing and with the bariatric procedures both the excess weight and the prevalence of these related diseases are decreasing. Both obesity and related diseases lead to impairment on health-related quality of life of the patients. We aimed to evaluate the short-term effects of sleeve gastrectomy operation on health related quality of life in patients that were operated for morbid obesity. Methods: Prospectively 62 patients that had sleeve gastrectomy operation enrolled in the study. The percentage of excess weight loss (%EWL) and the percentage of excess BMI loss (%EBMIL) were calculated 6 months after the operation. Anthropometric data and obesity-related co-morbidities were recorded. SF-36 questionnaire was used in order to evaluate the general health quality of the patients. Results: The mean age of the patients was 37 years and the majority of the patients were female (74.2%). At the postoperative 6th month, mean %EWL was calculated as 52.7% and mean %EBMIL was 60.1%. Six months after the operation, with the significant weight loss achieved, obesity-related co-morbidities were improved. Short Form-36 subscale scores at 6 months following the operation were observed, when compared with the preoperative scores (all p< 0.001). The mean physical health score significantly improved from 46.1 to 83.6 and the median mental health improved from 52 to 84, just 6 months after the sleeve gastrectomy operation. In multiple regression analysis %EWL was found to be a significant determinant of DMental health (B coefficient 0.490, p = 0.025) and D Physical health (B coefficient 0.388, p = 0.047) after adjusting for gender, age, smoking, obstructive sleep apnea syndrome, hypertension, diabetes mellitus and coronary disease. Conclusions: With the successive weight loss after sleeve gastrectomy, at the postoperative 6th month, the physical and mental health-related quality of life was significantly improved. Early and expedited regain of this quality of life after the operation is important for the patients and their social surroundings. Moreover it is important for the countries to decrease the medical expenses and increase labour productivity.